50 years and worlds apart: Rethinking the Holocene occupation of Cloggs Cave (East Gippsland, SE Australia) five decades after its initial archaeological excavation and in light of GunaiKurnai world views. Issue 1 (2nd January 2021) - David, Bruno; Fresløv, Joanna; Mullett, Russell; ,; Delannoy, Jean-Jacques; McDowell, Matthew; Urwin, Chris; Mialanes, Jerome; Petchey, Fiona; Wood, Rachel; Russell, Lynette; Arnold, Lee J.; et al.
Abstract: In this paper we report on new research at the iconic archaeological site of Cloggs Cave (GunaiKurnai Country), in the southern foothills of SE Australia's Great Dividing Range. Detailed chronometric dating, combined with high-resolution 3D mapping, geomorphological studies and archaeological excavations, now allow a dense sequence of Late Holocene ash layers and their contents to be correlated with GunaiKurnai ethnography and current knowledge. These results suggest a critical re-interpretation of what the Old People were, and were not, doing in Cloggs Cave during the Late Holocene. Instead of a lack of Late Holocene cave occupation, as previously thought through the conceptual lens of 'habitat and economy', Cloggs Cave is now understood to have been actively used for special, magical purposes. Configured by local GunaiKurnai cosmology, cave landscapes (including Cloggs Cave's) were populated not only by food species animals, but also by 'supernatural' Beings and forces whose presence helped inform occupational patterns. The profound differences between the old and new archaeological interpretations of Cloggs Cave, separated by five decades of developing archaeological thought and technical advances, draw attention to archaeological meaning-making and highlight the significance of data capture and the pre-conceptions that shape the production of archaeological stories and identities of place.